Pulmonary Function and Serum Carboxymethyl-Lysine Level Evaluation in Acromegaly Patients - (:unkn) unknown (My University, 2021)
Objective: We aimed to evaluate the pulmonary function tests (PFTs) and serum carboxymethyl-lysine (CML) level and their asso- ciation with the disease activity in patients with acromegaly. Mate- rial and Methods: This cross-sectional study included 65 acromegalic patients (F/M:28/37) and 52 controls ( F/M:23/29). PFTs such as spirometry and diffusing capacity of the lungs for carbon mo- noxide (DLCO) were performed to determine the lungs’ ability to exc- hange gases. Serum CML levels were measured with the enzyme-linked immunosorbent assay. Basal and nadir growth hor- mone (GH), hemoglobin A1c (HbA1c), and insulin-like growth factor- 1 (IGF-1) were also assessed. Results: Serum CML levels were significantly higher in acromegalic patients (208.1±80 ng/mL) than in controls (174.2±11 ng/mL), (p=0.02). The evaluated PFTs were expressed as predicted values [forced expiratory volume in the 1st second % (p=0.01), forced vital capacity % (p=0.007), functional residual capacity % (p=0.03), residual volume % (p=0.03), vital ca- pacity % (p=0.007), total lung capacity % (p=0.01), and DLCO% (p=0.02)] that were found to be elevated in acromegalic patients than in controls. CML levels positively correlated with HbA1c (r=0.53, p=0.02) but did not correlate with basal GH levels (r=0.35, p=0.06). GH and IGF-1 levels positively correlated with lung volume in acro- megalic patients. Conclusion: Serum CML levels increased in acro- megaly patients but had no association with the PFTs results. Increased lung volume was the most prominent lung function altera- tion in acromegalic patients; relevantly, we found elevated GH and IGF-1 levels to be associated with the increased lung volumes. Future studies need to evaluate the association between the advanced glycation end-products and complications of acromega

Amaç: Bu çalışmada akromegali hastalarında solunum fonksiyonları, serum karboksimetil-lizin [carboxymethyl-lysine (CML)] seviyeleri ve hastalık aktiviyeleriyle ilişkilerini değerlendirmeyi amaçladık. Gereç ve Yöntemler: Bu kesitsel çalışmaya 65 akromegali hastası (K/E: 28/37) ve 52 kontrol (K/E: 23/29) olgusu dâhil edilmistir. Solunum fonksiyon testleri (SFT) spirometri ile gaz değişimi ise karbon monoksit difüzyon kapasitesi [diffusing capacity of the lungs for carbon monoxide (DLCO)] ile değerlendirilmiştir. Serum CML düzeyi enzim bağımlı immünosor- bent ölçüm metoduyla ölçülmüştür. Hemoglobin A1c (HbA1c), insülin benzeri büyüme faktörü-1 [insulin-like growth factor-1 (IGF-1)], bazal ve nadir büyüme hormonu (BH) düzeyleri ölçülmüştür. Bulgular: Serum CML seviyeleri akromegali hastalarında (208,1±80 ng/mL), kontrol hastalarına göre (174,2±11 ng/mL) belirgin olarak daha yük- sekti (p=0,02). SFT ve DLCO; akromegali hastalarında kontrol grubuna göre anlamlı olarak daha yüksek saptandı [% birinci saniyedeki zorlu ekspiratuar volüm (p=0,01), % zorlu vital kapasite (p=0,007), % fonk- siyonel rezidüel kapasite (p=0,03), % kalıntı hacim (p=0,03), % vital kapasite (p=0,007), % total akciğer kapasitesi (p=0,01) ve %DLCO (p=0,02)]. CML düzeyi; HbA1c ile pozitif korelasyon gösterirken, (r=0.53, p=0.02), bazal BH ile korelasyon mevcut değildi (r=0.35, p=0.06). Akromegali hastalarında BH ve IGF-1 düzeyleriyle akciğer kapasitesi arasında pozitif korelasyon mevcuttu. Sonuç: Serum CML düzeyleri akromegali hastalarında yükselmiştir, ancak SFT ile arasında bir ilişki gösterilememiştir. Artmış akciğer kapasitesi akromegali hasta- larında en sık görülen solunum fonksiyon değişikliğidir ve artmış BH ve IGF-1 düzeyleriyle arasında bir ilişki mevcuttu. İleri glikasyon son ürün- leri ve akromegali komplikasyonları arasındaki ilişkinin gösterilebilmesi için daha fazla çalışmaya ihtiyaç vardır.
Akromegali Hastalarında Solunum Fonksiyonu ve Serum Karboksimetil-Lizin Seviyesinin Değerlendirilmesi